FAKTOR DETERMINAN PERDARAHAN POST PARTUM PADA IBU BERSALIN - Yulida Effendi Nasution; Mayang Wulan (Nursing Arts, 2023)
According to the World Health Organization (WHO) bleeding occupies the highest percentage of causes of maternal death (28%), preeclampsia/eclampsia (24%), infection (11%), while indirect causes are obstetric trauma 5% and others (11%) . The aim of the study was to determine the factors associated with post partum bleeding in mothers giving birth at the Ridho Primary Clinic. The research design used in this study was an analytic survey with a cross sectional approach. The population in this study were 54 mothers who experienced postpartum hemorrhage. Sampling in this study using total sampling where all populations were sampled as many as 54 people. The results of the bivariate analysis showed that there was a relationship between the age factor (p_value = 0.004), the parity factor (p_value = 0.001), the birth spacing factor (p_value = 0.002) and post-partum bleeding in women giving birth. The conclusion of this study is that there is a relationship between age, parity and birth spacing with post partum haemorrhage in women giving birth at the Ridho Primary Clinic. Suggestions for health workers are expected to always provide information and counseling to pregnant and giving birth women about postpartum hemorrhage so that these cases can be reduced and treated as early as possible.